Solid-polymer-surfactant complexes for enhancing the flow in pipelines - Zainab, Yousif Shnain (2016)
Eddies which arise as a result of the turbulent nature of fluids pumped through pipelines is a major challenge which contributes to drag. Such not only increases the time of liquid transportation, but contributes to massive energy dissipation. As a result, efforts are being made to contain these anomalies but a consensus has not been reached. Thus, the initiation of this current research. This work introduces an economically feasible technique for enhancing the drag reduction and mechanical degradation of known polymeric additives through the formation of certain complexes with polar surface active agents (surfactants). Such was achieved by using two polymeric additives: Polyacrylamide and Sodium Carboxyl Methyl Cellulose, two surfactants: Sodium Dodecyl-Benzene Sulfonate (SDS) and Triton X-45 and Nano particles of Fumed silica to form complexes. Three phases were involved in the experiment-the use of Rotating Disk Apparatus (RDA) to examine drag reduction, mechanical resistance and stability of the additives, the Transmission Electron Microscopy (TEM) to examine the morphology of the complexes, the drag reduction and shear stability of the investigated solutions using a closed loop pipeline system. Overall, the results obtained from all the stages of the experiment showed that drag reduction increased as the concentration increased. The highest drag reduction for polymer was 48% at 2000ppm while the complex of Polyacrylamide and Sodium dodecyl-benzene sulfonate gave 54% which made complexes better. This showed optimum performance against their 33% and 35% respective individual DR. Adding fume silica to this mixture inhibits their degradation and yielded %DR of (47, 48, 51, 54, 58), (45, 48, 54, 55, 57) and (56, 57, 61, 63, 68) for polymer-surfactant-fumed-silica powder at (500, 1000, 1500, 1700, 2000)PPM concentration respectively.However, the pipe results obtained for 2000ppm was 7826.618. Results for (PAM-Triton X-45-fumed silica) complex was 85.8 % drag reduction and for fumed silica-Triton X-45 complex (fumed silica-PAM), it was 79.2% and 76.7% respectively. Other results such as fumed silica alone, surfactant solution and polymer at 2000ppm showed 63.2 %, 62.6% and 59.5% drag reduction respectively. Overall, about 85.8% DR was achieved in the study, which is the power saving possible in transporting the fluid through pipelines. A mathematical expression was developed to delineate the real mechanism of DR. As a conclusion, new, greener DRAs were successfully introduced and their effectiveness in improving the flow was proven experimentally. According to the TEM images, it is confirmed that complexes are effectively formed in the present work and new aggregated structure can contribute significantly to the drag reduction and polymer shear resistance enhancement.